2021
DOI: 10.1162/edfp_a_00326
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Unions, Collective Bargaining, and the Response to COVID-19

Abstract: In response to the COVID-19 crisis, school districts worked quickly to roll out distance learning plans in the spring. Sometimes these plans impinged upon or were directly in conflict with provisions found in collective bargaining agreements (CBAs) negotiated between teachers' unions and district administration. In this brief, we unpack how urban school systems changed CBAs to make way for learning under COVID-19 conditions. We review COVID-19-related contract changes in one hundred and one urban school distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Under these circumstances, administrators have been central to managing the crisis and will ultimately play a key role in successfully overseeing their institution until some semblance of normality resumes. Hemphill and Marianno [64] stated that school administrators have to carefully review and manage the working conditions of their teachers, the environment of working with such uncertainty, and the learning needs of their students during the pandemic. These factors have made it essential to investigate the interaction of phobia, work-life balance, and life satisfaction experienced by school administrators during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, administrators have been central to managing the crisis and will ultimately play a key role in successfully overseeing their institution until some semblance of normality resumes. Hemphill and Marianno [64] stated that school administrators have to carefully review and manage the working conditions of their teachers, the environment of working with such uncertainty, and the learning needs of their students during the pandemic. These factors have made it essential to investigate the interaction of phobia, work-life balance, and life satisfaction experienced by school administrators during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…There is not yet much evidence relating teachers' unions and school districts' responses to COVID-19. Hemphill and Marianno (2020) found that teachers' unions renegotiated collective bargaining agreements in response to COVID-19 in 25 of the 101 reviewed public school districts. Valant (2020) observed that the reopening decisions of 256 public school districts reported by Education Week were significantly correlated with the share of Trump voters in the county in the 2016 presidential election, but not statistically related to COVID-19 cases per capita in the county.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of our measures of second face power is a dichotomous indicator for whether the school district has a CBA. Collective bargaining creates a direct channel for teachers’ unions to influence reopening plans as many of the working condition changes required by the movement from in-person to remote instruction or from remote back to in-person instruction are required to be negotiated with teachers’ unions (Hemphill & Marianno, 2021). Collective bargaining gives teachers’ unions a legal voice in policies that affect working requirements for their teacher membership, and thus the opportunity to proactively shape a school district’s policy agenda.…”
Section: Datamentioning
confidence: 99%